Hollow Mesoporous Metal‐Organic Framework Microdisks via a Solid Template‐Based Approach and Post‐Synthetic Wet‐Chemical Etching for Protein Loading. Issue 4 (28th February 2020) - Zhu, Guixian; Cheng, Lin; Qi, Ruogu; Liu, Xuewu
Abstract: Metal‐organic frameworks (MOFs), with high crystalline and ordered pore structures, hold great potential for various applications. However, the small microporous structures of MOFs restrict their applications. MOFs with larger porous structure and dimensions can expand their functionality to integrate with other large active agents. By applying porous silicon microdisks (PSi) as hard templates, zeolitic imidazolate frameworks (ZIFs) were assembled on PSi to form PSi@ZIF‐8 core‐shell microdisks. A new porous structure of ZIF‐8 microcages was obtained via a post‐synthetic approach. The influence of PSi and reaction precursor for ZIF‐8 were explored, and the formation mechanism of mesoporous ZIF‐8 (PZIF‐8) hollow microcages was also proposed. By applying bovine serum albumin (BSA) as a loading agent, the protein release behavior of PSi@PZIF‐8 was investigated. It is noted that prepared PZIF‐8 microcages could serve as new vectors for loading active agents. Abstract : Mesoporous ZIF‐8 (PZIF‐8) hollow microcages are prepared through synthetic wet‐chemical etching by applying porous silicon microdisks (PSi) as hard templates. It is the property of ZIFs that promotes the formation of porous hollow structures on shells. On the basis of the mesoporous structure, the protein release behavior of PSi@PZIF‐8 was investigated by applying BSA as a model protein. The results showed that ZIF‐8 film can prolong protein release.